Blockchain Technology Applications in Businesses and Organizations (Hershey, USA: Business Science Reference (IGI Global), 2022)
"This book investigates the true advantages that blockchain entails for firms by creating transparent and digital transactions, resolving conflicts and exceptions, and providing incentive-based mechanisms and smart contracts"-- Provided by publisher.
Keywords: Electronic commerce; Blockchains (Databases); Business enterprises--Technological innovations